2018 American Heart Association Focused Update on Advanced Cardiovascular Life Support Use of Antiarrhythmic Drugs During and Immediately After Cardiac Arrest: An Update to the American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care. Issue 23 (4th December 2018) - Panchal, Ashish R.; Berg, Katherine M.; Kudenchuk, Peter J.; Del Rios, Marina; Hirsch, Karen G.; Link, Mark S.; Kurz, Michael C.; Chan, Paul S.; Cabañas, José G.; Morley, Peter T.; Hazinski, Mary Fran; Donnino, Michael W.
Abstract : Antiarrhythmic medications are commonly administered during and immediately after a ventricular fibrillation/pulseless ventricular tachycardia cardiac arrest. However, it is unclear whether these medications improve patient outcomes. This 2018 American Heart Association focused update on advanced cardiovascular life support guidelines summarizes the most recent published evidence for and recommendations on the use of antiarrhythmic drugs during and immediately after shock-refractory ventricular fibrillation/pulseless ventricular tachycardia cardiac arrest. This article includes the revised recommendation that providers may consider either amiodarone or lidocaine to treat shock-refractory ventricular fibrillation/pulseless ventricular tachycardia cardiac arrest.